FACTORS THAT AFFECT EFL STUDENTS' DIFFICULTY IN READING COMPREHENSION - Guna, Alprian (University of Darussalam Gontor, 2023)
This study aims to discover the internal factors that affect EFL students' difficulty in reading comprehension. The research participants in this study were five English as Foreign Language (EFL) students who could not achieve the grade standard in a Reading class at the English Language Education Program (ELEP) in a small town in Central Java. The Interviews were used as the instruments to collect the data. In the interview, 5 participants were asked about the internal factors that affected students' difficulties in reading comprehension. The thematic analysis revealed that students' difficulty in reading comprehension is affected by two primary internal factors. The first factor pertains to students' ability, encompassing their grammatical and vocabulary knowledge in English. The second factor encompasses students’ perceptions including feelings of interest, boredom, anxiety, sickness, and personal problems.